A partial loss-of-function variant in AKT2 is associated with reduced insulin-mediated glucose uptake in multiple insulin sensitive tissues: a genotype-based callback positron emission tomography study - Latva-Rasku, A; Honka, M; Stančáková, A; Koistinen, H; Kuusisto, J; Guan, L; Manning, A; Stringham, H; Gloyn, A; Lindgren, C; Collins, F; Mohlke, K; et al. (American Diabetes Association, 2017)
Rare fully penetrant mutations in AKT2 are an established cause of monogenic disorders of glucose metabolism. Recently, a novel partial loss-of-function AKT2 coding variant (p.Pro50Thr) was identified that is nearly specific to Finns (frequency 1.1%), with the low-frequency allele associated with an increase in fasting plasma insulin level and risk of type 2 diabetes. The effects of p.Pro50Thr on insulin-stimulated glucose uptake (GU) in the whole body and in different tissues have not previously been investigated. We identified carriers (N=20) and matched non-carriers (N=25) for this allele in the population-based METSIM study and invited these individuals back for positron emission tomography study with [(18)F]-fluorodeoxyglucose during euglycemic hyperinsulinemia. When we compared p.P50T/AKT2 carriers to non-carriers, we found a 39.4% reduction in whole body GU (P=0.006) and a 55.6% increase in the rate of endogenous glucose production (P=0.038). We found significant reductions in GU in multiple tissues: skeletal muscle (36.4%), liver (16.1%), brown adipose (29.7%), and bone marrow (32.9%), and increases of 16.8-19.1% in 7 tested brain regions. These data demonstrate that the P50T substitution of AKT2 influences insulin-mediated GU in multiple insulin sensitive tissues, and may explain, at least in part, the increased risk of type 2 diabetes in p.P50T/AKT2 carriers.